Experience of tinnitus in adults who have severe-to-profound hearing loss: A scoping review - Alzahrani, Lama; Sereda, Magdalena; Chamouton, Carla Salles; Haider, Háula; Dewey, Rebecca Susan; Hoare, Derek J. (Frontiers in Neurology, 2022)
Background Tinnitus is defined as the subjective perception of sound in the absence of an external stimulus, and tinnitus disorder becomes relevant when it is associated with emotional distress, cognitive dysfunction, and/or autonomic arousal. Hearing loss is recognized as the main risk factor for the pathogenesis of tinnitus. However, clinical guidelines for tinnitus disorder provide little direction for those who have severe-to-profound hearing loss including those who are pre-lingually Deaf. The aim of this scoping review was to catalogue what is known from the existing literature regarding the experience and management of tinnitus in adults who have a severe-to-profound hearing loss. Summary A scoping review was conducted following the Preferred Reporting Item for Systematic Reviews and Meta-analysis extension for Scoping Reviews. Records were included if they reported an evaluation of tinnitus in adults who had severe-to-profound hearing loss. The online databases Ovid (MEDLINE, EMBASE and PsycINFO), CINAHL, ProQuest, Scopus, and Google Scholar were searched using the search terms ‘tinnitus’ (as a MESH term) and ‘deaf’ OR ‘profound hearing loss. Thirty-five records met the inclusion criteria for this review and were cataloged according to three major themes: Impact of tinnitus in deaf adults; Primary treatment of tinnitus in deaf adults; and Cochlear implant studies where tinnitus was a secondary outcome. Tinnitus symptom severity was assessed before and after intervention using tinnitus validated questionnaires in 29 records, with six further records using other assessment tools to measure tinnitus severity. Participants using cochlear implants were included in 30 studies. Medication, repetitive transcranial magnetic stimulation (rTMS), electrical promontory stimulation, and behavioral self-control therapy were each reported in single records. Key messages This scoping review cataloged the experience, assessment, and treatment of tinnitus in adults who have severe-to-profound hearing loss. It is shown that there is very limited research reported in this field. Although this review included many records, most focused on the provision of cochlear implants for severe-to-profound hearing loss, with assessment and measurement of tinnitus as a baseline or secondary outcome. Largely missing in the literature are empirical studies that seek firstly to understand the nature of the experience of tinnitus by people with no or little residual access to external sound.